Minimally invasive surgery via bilateral thoracotomy for treating left ventricular aneurysm with concomitant ventricular septal rupture - Qianzhen Li; Xiaodong Chen; Weiye Xu; Liangwan Chen (Journal of Cardiothoracic Surgery)
Abstract Background Full median sternotomy is the traditional approach for the treatment of left ventricular aneurysms (LVA) with or without concomitant ventricular septal rupture (VSR). However, it has some disadvantages such as reduced breathing and exercise thoracic stability, which may increase the surgical risk for older or fragile patients. Herein, we report a case of successful minimally invasive bilateral thoracotomy. Patient and method A 79-year-old male patient visited our center complaining of breathlessness and orthopnea 21 days after an acute myocardial infarction and percutaneous coronary intervention. An LVA (34.7 mm × 44.4 mm) and a VSR with a diameter of 10 mm close to the apex was detected by echocardiography. Bilateral thoracotomy was performed via two incisions: a 3 cm incision at the right 3rd intercostal space for the aortic root and left atrium vent cannula and aortic clamping; a 7 cm incision at the left 5th intercostal space to expose the apex for LVA and VSR repair. The patient was discharged 7 days postoperatively without any complications. Conclusion LVA with or without VSR can be successfully repaired via bilateral thoracotomy with promising outcomes.